Identifying Training Needs And Client Satisfaction Of Vocational Rehabilitation Services For Students With Physical, Intellectual, Or Multiple Disabilities In Kuwait - O. Al Fawair, Ahmad (M.j.) (2013)
Keperluan latihan dan kepuasan pelanggan adalah dua kebimbangan utama dalam pemulihan vokasional tetapi belum ditangani di Kuwait.